KOLABORASI TRIPLE HELIX PROSES KOMERSIALISASI DAN PROSES PRODUKSI PRODUK BARU INCINERATOR BUMDES NGINGAS MAKMUR ABADI - Handiwibowo, Gogor Arif; Hakim Nasution, Arman; Nadlifatin, Reny; Rosdiana Noer, Lissa (Universitas katolik Musi Charitas, 2022)
The BUMDes Ngingas Makmur Abadi incinerator is a new product created by the management to become a mainstay product and can provide benefits for BUMDes. From a deeper angel, this product still requires a lot of touches so that the commercialization process and the production process of this incinerator product can run perfectly. The triple helix concept is used to analyze the involvement of each element in the commercialization process and the production process of this incinerator product. The elements involved are Ngingas Village Government, Institut Teknologi Sepuluh Nopember (ITS) – Surabaya and PT. Boma Bisma Indra (Persero). The results of the analysis show that each element has had a role in the commercialization process and the production process of this incinerator product. However, there are still many roles that can be developed and explored from each element so that the commercialization process and the production process of this incinerator product can be better.